HIGH-PRESSURE OPTICAL SPECTROSCOPY AND X-RAY DIFFRACTION STUDIES ON SYNTHETIC COBALT ALUMINUM SILICATE GARNET - Taran M.N.; Nestola F.; Ohashi H.; Koch-Müller M.; Balic-Zunic T.; Olsen L.A. (My University, 2007)
The pressure-induced behavior of spin-allowed dd-bands of VIIICo2+ in the absorption spectra of synthetic CO3Al2Si3O12 garnet was studied from 10-4 to 13 GPa. The plots of the peak energy vs. pressure for the three sharpest well resolved bands at ca. 5160, 17 680, and 18 740 cm-1 display small but discernible breaks in linear relations between 4 and 5 GPa. Data from single-crystal X-ray diffraction likewise show discontinuities in trends of CoO8 polyhedral volume and distortion, and Co-O and Si-O bond distances over this pressure range. These effects are related to a pressure-induced phase transition from the β- to α-isostructural polymorph of CO3Al2Si3O12.
Keywords: COBALT-BEARING GARNET; HIGH-PRESSURE OPTICAL SPECTROSCOPY; HIGH-PRESSURE X-RAY DIFFRACTION; PHASE TRANSITIONS